Mental Health Concern during COVID-19 Pandemic in Nepal - Chalise, Anisha; Paudel, Shishir (Europasian Journal of Medical Sciences, 2020)
The whole world is struggling to combat COVID-19 pandemic forcing nations to take extreme measures in an attempt to prevent outbreaks and save lives. It has been noted that COVID-19 has established itself as a risk factor for psychological distress among the population of different subgroups. There are several factors such as uncertainties, controversies, misinformation, social isolation, stigma, and discrimination which are escalating the risk of massive mental distress among the public. Nepal is trying to increase its effort to combat COVID-19 by adopting community containment measures, but the mental health of the frontline health workforce, service providers, and the general public seems to be highly overshadowed. In this aspect, this paper aims to shed light on different aspects of mental health issues emerging in Nepal during the time of COVID-19 lockdown, along with some of its potential contributing factors. Nepal lacks adequate infrastructure and human resource to provide mental healthcare services effectively in case of any massive mental distress. In this state of resource deprivation, providing education and training regarding psychosocial issues to health system leaders, first responders, and health care professionals could be a key to address the population need at present and to prevent further complications.